1997
DOI: 10.1104/pp.115.4.1557
|View full text |Cite
|
Sign up to set email alerts
|

RNase Activity Prevents the Growth of a Fungal Pathogen in Tobacco Leaves and Increases upon Induction of Systemic Acquired Resistance with Elicitin

Abstract: The hypersensitive response and systemic acquired resistance (SAR) can be induced in tobacco (Nicotiana tabacum 1.) plants by cryptogein, an elicitin secreted by Pbytopbfbora crypfogea. Stem application of cryptogein leads to the establishment of acquired resistance to subsequent leaf infection with Pbytopbfbora parasitica var nicotianae, the agent of the tobacco black shank disease. We have studied early events that occur after the infection and show here that a tobacco gene encoding the extracellular S-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 39 publications
2
66
0
Order By: Relevance
“…This suggestion was strongly supported by several investigators [43,44] who reported that RNase gene expression and activity often increase in response to pathogen attack. Moreover, Booker [45] reported that Ribonucleases (RNases) degrade RNA and exert a major influence on gene expression during development and in response to biotic and abiotic stresses.…”
Section: Discussionmentioning
confidence: 63%
“…This suggestion was strongly supported by several investigators [43,44] who reported that RNase gene expression and activity often increase in response to pathogen attack. Moreover, Booker [45] reported that Ribonucleases (RNases) degrade RNA and exert a major influence on gene expression during development and in response to biotic and abiotic stresses.…”
Section: Discussionmentioning
confidence: 63%
“…Notably, LRR1 potentiates the RNase activity of PR10. RNase activity is thought to be essential for the resistance response to microbial pathogens (Barna et al, 1989;Lusso and Kuc, 1995;Galiana et al, 1997;Shivakumar et al, 2000;Park et al, 2004). In this study, LRR1 is also shown to be a potential stimulator of PR10 phosphorylation, which could lead to the activation of defense and HR-like cell death.…”
Section: Lrr1 Promotes the Ribonuclease Activity And Phosphorylation mentioning
confidence: 68%
“…In addition it was shown that UE treatment up-regulated other defence genes whose induction by marine algal elicitors was not previously reported, notably genes encoding cell wall proteins, calmodulin, ribonuclease, aquaporin and HSR203. Previous reports have indicated that these genes respond to elicitor treatments and/or pathogen attack (Oppermann, Taylor & Conkling 1994;Chappell et al 1997;Galiana et al 1997;Garcia-Muniz, Martinez-Izquierdo & Puigdomenech 1998;Ali et al 2003).…”
Section: Discussionmentioning
confidence: 99%